Combined Chaetocin/Trichostatin A Treatment Improves the Epigenetic Modification and Developmental Competence of Porcine Somatic Cell Nuclear Transfer Embryos - Jeong, Pil-Soo; Yang, Hae-Jun; Park, Soo-Hyun; Gwon, Min Ah; Joo, Ye Eun; Kim, Min Ju; Kang, Hyo-Gu; Lee, Sanghoon; Park, Young-Ho; Song, Bong-Seok; Kim, Sun-Uk; Koo, Deog-Bon; et al. (Frontiers in Cell and Developmental Biology, 2021)
Developmental defects in somatic cell nuclear transfer (SCNT) embryos are principally attributable to incomplete epigenetic reprogramming. Small-molecule inhibitors such as histone methyltransferase inhibitors (HMTi) and histone deacetylase inhibitors (HDACi) have been used to improve reprogramming efficiency of SCNT embryos. However, their possible synergistic effect on epigenetic reprogramming has not been studied. In this study, we explored whether combined treatment with an HMTi (chaetocin) and an HDACi (trichostatin A; TSA) synergistically enhanced epigenetic reprogramming and the developmental competence of porcine SCNT embryos. Chaetocin, TSA, and the combination significantly increased the cleavage and blastocyst formation rate, hatching/hatched blastocyst rate, and cell numbers and survival rate compared to control. In particular, the combined treatment improved the rate of development into blastocysts more so than chaetocin or TSA alone. TSA and combined chaetocin/TSA significantly reduced the H3K9me3 levels and increased the H3K9ac levels in SCNT embryos, although chaetocin alone significantly reduced only the H3K9me3 levels. Moreover, these inhibitors also decreased global DNA methylation in SCNT embryos. In addition, the expression of zygotic genome activation- and imprinting-related genes were increased by chaetocin or TSA, and more so by the combination, to levels similar to those of in vitro-fertilized embryos. These results suggest that combined chaetocin/TSA have synergistic effects on improving the developmental competences by regulating epigenetic reprogramming and correcting developmental potential-related gene expression in porcine SCNT embryos. Therefore, these strategies may contribute to the generation of transgenic pigs for biomedical researches.